Research Data Management Services - Chukwusa, Joseph; Oshiokpu, Edith Ijeoma (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
This study investigated Research Data Management (RDM) services among 3 selected University libraries in South-South, Nigeria. The descriptive survey design was employed in this research. Due to the fact that the population was small (75 respondents) all of them was used for the study. However, after questionnaire administration and retrieval, 72 of the respondents were used for the study. Frequency count and mean statistics were deployed in analyzing the data. Result of the study revealed that the awareness level of (RDM) services amongst the librarians was high; and so was the extent of implementation of RDM. The research recommended that it is imperative that Nigerian libraries and librarians acquire deeper understanding regarding the extent and scope of research data management services so that they can understand where to improve on.